2019
DOI: 10.3389/fpls.2019.01475
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Levels in Brassicaceae Microgreens Increase Under Tailored Light-Emitting Diode Spectra

Abstract: To increase the nutritional value and levels of essential minerals in vegetable food, microgreens are promising targets. The metabolic processes of microgreens can be managed with different cultivation techniques, which include manipulating the properties of light derived by light-emitting diodes (LEDs). In this study Brassicaceae microgreens (kohlrabi Brassica oleracea var. gongylodes, broccoli Brassica oleracea, and mizuna Brassica rapa var. Japonica) were cultivated under different light spectral quality, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
4
36
1
Order By: Relevance
“…The highest TAA content was 390.6 mg 100 g −1 fw, registered for rocket × C, while the lowest content was 219.5 mg 100 g −1 fw, registered for cabbage × NS. Ascorbic acid is a powerful water-soluble antioxidant [18]; it is a typical example of an imperative secondary metabolite that acts as enzymes 'cofactor, regulates the photosynthesis and cell division, other than being involved in the transduction of signals in plants [10], and inhibits the N-nitroso compounds deriving from nitrite [44]. The TAA values obtained for Brussels sprouts were consistent with those obtained by Xiao et al [45], where they were higher than those registered for cabbage.…”
Section: Microgreens Total Ascorbic Acid Content and Total Anthocyaninssupporting
confidence: 79%
See 1 more Smart Citation
“…The highest TAA content was 390.6 mg 100 g −1 fw, registered for rocket × C, while the lowest content was 219.5 mg 100 g −1 fw, registered for cabbage × NS. Ascorbic acid is a powerful water-soluble antioxidant [18]; it is a typical example of an imperative secondary metabolite that acts as enzymes 'cofactor, regulates the photosynthesis and cell division, other than being involved in the transduction of signals in plants [10], and inhibits the N-nitroso compounds deriving from nitrite [44]. The TAA values obtained for Brussels sprouts were consistent with those obtained by Xiao et al [45], where they were higher than those registered for cabbage.…”
Section: Microgreens Total Ascorbic Acid Content and Total Anthocyaninssupporting
confidence: 79%
“…Brassica vegetables are widely planted and consumed all over the world [6][7][8][9][10], including Brussels sprouts, broccoli, cabbage, cauliflower, etc. [6,10], representing a multitude of edible organs such as roots, bulbs, heads and leaves and offering an enormous array of plant secondary metabolites [6]. Cartea et al [8] stated that Brassica vegetables induce health enhancement through their complex blend of antioxidant phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Since ROS are constantly produced by metabolically active plants, enhancing compounds like AA and other antioxidant compounds is important for mitigating plant cellular damage. A recent study found supplementary yellow (595 nm) to red and blue components increased AA content in kohlrabi microgreens, but the same effect was not observed in mizuna and broccoli microgreens (Samuolienė et al, 2019). Although our study did not examine the AA content, we determined the antioxidant activity according to an ascorbic acid standard (Figure 4d-f).…”
Section: Frapmentioning
confidence: 72%
“…The content of total carotenoids in broccoli cultivated in autumn (26 mg/kg) represented a 2.8-fold increase compared to broccoli grown in spring (9 mg/kg). Although the effect of sunlight on the biosynthesis of Brassica carotenoids is not clear [ 10 ], in florets of the broccoli variety ‘Green’ the control group showed higher levels when compared with samples subjected to light of different wavelengths [ 54 , 55 ]. Moreover, other authors have reported that temperatures >15 °C could lead to a decrease in carotenoids [ 8 ].…”
Section: Resultsmentioning
confidence: 99%